2019
DOI: 10.1159/000496036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Low-Molecular-Weight Hyaluronic Acid-Based Treatment on Onset of Acute Side Effects in Women Receiving Adjuvant Radiotherapy after Cervical Surgery: A Randomized Clinical Trial

Abstract: Background: Radiotherapy treatment for cervical cancer (CC) often induces side effects, including inflammation, dryness, dyspareunia. Considering its key role in the healing process, hyaluronic acid (HA) could be useful for the completion of radiotherapy. Objectives: The aim of this work was to evaluate the ability of HA to reduce the onset of side effects due to radiotherapy. Materials and Methods: In total, 180 women undergoing radiotherapy were randomized into two arms: controls and those treated with vagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…That is, cervical cancer patients with stage Ia1–IIa2 are treated with comprehensive treatment measures mainly with surgery and supplemented with radiotherapy; patients with stage ≥IIb are treated with simultaneous radiotherapy and chemotherapy with radiotherapy as the core ( 7 , 11 ). However, it has been observed that after cervical cancer surgery, the sense of experience such as pain or incompleteness caused by surgical resection can lead to a range of negative emotions such as low self-esteem, loss, and depression ( 12 , 13 ); Damage to adjacent organs, fatigue or bone marrow suppression caused by radiotherapy can cause further damage to the patient's health status and quality of life ( 14 , 15 ); Moreover, the damage to the digestive tract caused by chemotherapy can lead to decreased appetite, nausea and vomiting, and even rejection of food, and the patient's nutrient intake is insufficient, and the body's immunity can be further reduced ( 16 , 17 ). These problems can lead to non-compliance or intolerance of patients to later radiotherapy and chemotherapy, and patients end up in the unfavorable situation of short survival time and low survival probability because they cannot complete their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…That is, cervical cancer patients with stage Ia1–IIa2 are treated with comprehensive treatment measures mainly with surgery and supplemented with radiotherapy; patients with stage ≥IIb are treated with simultaneous radiotherapy and chemotherapy with radiotherapy as the core ( 7 , 11 ). However, it has been observed that after cervical cancer surgery, the sense of experience such as pain or incompleteness caused by surgical resection can lead to a range of negative emotions such as low self-esteem, loss, and depression ( 12 , 13 ); Damage to adjacent organs, fatigue or bone marrow suppression caused by radiotherapy can cause further damage to the patient's health status and quality of life ( 14 , 15 ); Moreover, the damage to the digestive tract caused by chemotherapy can lead to decreased appetite, nausea and vomiting, and even rejection of food, and the patient's nutrient intake is insufficient, and the body's immunity can be further reduced ( 16 , 17 ). These problems can lead to non-compliance or intolerance of patients to later radiotherapy and chemotherapy, and patients end up in the unfavorable situation of short survival time and low survival probability because they cannot complete their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments are also particularly useful for BCS women [38] and cervical cancer survivors [39].…”
Section: Other Alternativesmentioning
confidence: 99%
“…Its use has been studied in cancer patients post-radiotherapy and brachytherapy to prevent and treat late vaginal sequalae. Several authors have shown symptomatic improvement in dyspareunia, sexual function and dryness with a few months of treatment in a high proportion of patients (70e90%) [29]. Some preparations also include vitamins A and E together with hyaluronic acid.…”
Section: Treatment Strategies For Female Sexual Dysfunctionmentioning
confidence: 99%